Ofatumumab – a valid treatment option for chronic lymphocytic leukemia patients - AlDallal SM (Dove Medical Press, 2017)
Salma M AlDallal Haematology Laboratory, Amiri Hospital, Kuwait City, Kuwait Abstract: Ofatumumab Arzerra® is a human monoclonal antibody, which induces killing of a panel of tumor B-cell lines and primary tumor cells by the activation of in vitro complement-dependent cytotoxicity and antibody-dependent, cell-mediated cytotoxicity. The humanized anti-CD20 monoclonal antibody has been approved by the US Food and Drug Administration for the treatment of chronic lymphocytic leukemia patients. This article summarizes this antibody’s therapeutic effect on chronic lymphocytic leukemia. Keywords: ofatumumab, cell-mediated cytotoxicity, chronic lymphocytic leukemia